Knowledge and attitudes of offenders towards the performance of medical male circumcision in prisons of Gauteng Province, South Africa - Monkwe, Phaphe Declinda (My University, 2018)
The study was about the knowledge and attitudes of offenders towards the performance of medical male circumcision in prisons. The aim of the study was to determine and asses the knowledge and attitudes of offenders towards the performance of medical male circumcision in prisons. A quantitative study was conducted by using researcher-administered questionnaires at Leeuwkop Management area, maximum centre. A simple random sampling of two hundred and twenty-three male respondents was selected from all races and only two hundred and three managed to complete the questionnaires correctly. Data was analysed using Statistical package for the social sciences software program. Data was presented using descriptive and inferential statistics. More than half of the respondents were medically circumcised and less than half of the medically circumcised respondents had performed it in prisons. Most respondents were between the ages of 25-35 years and majority of them have shown fair knowledge and negative attitude towards the performance of medical male circumcision in prisons. It was recommended that thorough health education on the benefits of medical male circumcision should be stressed to offenders. For medical male circumcision programme to succeed, offenders should have adequate knowledge on male circumcision and its benefits.
Thesis (MPA.) -- University of Limpopo, 2018
Keywords: Offenders; Medical male circumcision; Prisons; Circumcision; Prisoners - medical care